Where the money is. - Francis, Wendy (American City & County, 2001)
According to the Salary Survey for IT/GIS Professionals for 2000, salaries for IT and GIS professionals vary according to employer, education, experience, and location. The document is an update of a 1998 survey and features much more detailed information about technology-related jobs. Results of the survey are discussed.